2021
DOI: 10.1080/0305764x.2021.1970718
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-school girls’ lives in Zimbabwe: what can we learn from a storytelling research approach?

Abstract: This paper focuses on the experiences of out-of-school girls in Zimbabwe. It draws on a research strand of SAGE (Supporting Adolescent Girls' Education), a UKAid programme funded through the Foreign, Commonwealth and Development Office's (FCDO) Girls' Education Challenge (GEC) initiative. Using a digital storytelling approach the research highlights critical events that have changed girls' lives and impacted on how they see their futures. The paper explores insights made possible by this alternative methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…While more girls compared to boys, complete primary school, the former drop out of secondary school more often than the latter do (UNDP 2020). Poverty is not the only reason, as observed by Buckler et al (2022) who cite many other publications, which point to school location, absent parents, religious beliefs, inadequate resources and teenage pregnancies as detrimental factors. Buckler et al (2022) have clearly shown, through interactions with adolescent out-of-school girls in Zimbabwe that they aspire to go to school and get a formal education, and are aware of the value it would have for their futures.…”
Section: Past To Present To the Desired Futurea Very Brief Literature...mentioning
confidence: 97%
See 1 more Smart Citation
“…While more girls compared to boys, complete primary school, the former drop out of secondary school more often than the latter do (UNDP 2020). Poverty is not the only reason, as observed by Buckler et al (2022) who cite many other publications, which point to school location, absent parents, religious beliefs, inadequate resources and teenage pregnancies as detrimental factors. Buckler et al (2022) have clearly shown, through interactions with adolescent out-of-school girls in Zimbabwe that they aspire to go to school and get a formal education, and are aware of the value it would have for their futures.…”
Section: Past To Present To the Desired Futurea Very Brief Literature...mentioning
confidence: 97%
“…Poverty is not the only reason, as observed by Buckler et al (2022) who cite many other publications, which point to school location, absent parents, religious beliefs, inadequate resources and teenage pregnancies as detrimental factors. Buckler et al (2022) have clearly shown, through interactions with adolescent out-of-school girls in Zimbabwe that they aspire to go to school and get a formal education, and are aware of the value it would have for their futures. Indeed, they are inspired by the fact that on date, with the perceptible improvement in gender parity, over half of provincial ministers, close to one-third of cabinet ministers, one-fifth of ambassadors, more than half of permanent secretaries in public service, and one-third of senior and middle-level managers in the corporate sector, are women (UNDP 2020), and thanks to the policies Zimbabwe has in place to promote gender equality in health, education and political leadership, girls today who attend school, can pursue their dreams with hope, and look forward to a better tomorrow for themselves.…”
Section: Past To Present To the Desired Futurea Very Brief Literature...mentioning
confidence: 97%
“…This relationship makes forming and achieving aspirations a multidimensional and complex journey. However, Buckler et al (2021) note that the disadvantaged states leading to such complexity should be viewed as non-static, as individual experiences and contexts evolve over time.…”
Section: Capabilities Aspirations and Political Povertymentioning
confidence: 99%